Diet and nutrition information and support needs in pelvic radiotherapy: A systematic, mixed‐methods review. (26th August 2020) - Saltaouras, Georgios; Lightowler, Helen; Coe, Shelly; Watson, Eila K.
Abstract: Introduction: This study aimed to review diet and nutrition information and support needs of cancer patients who receive pelvic radiotherapy to inform the development of interventions to improve this area of care. Methods: The systematic review followed the PRISMA guidelines. Six electronic databases were searched for peer‐reviewed studies of any design that assessed diet and nutrition needs after a pelvic cancer diagnosis. Narrative synthesis was used to integrate findings. Results: Thirty studies (12 quantitative, 15 qualitative, 3 mixed‐methods) were included. Four themes, "content of dietary information"; "sources of information"; "sustaining dietary change"; and "views on the role of diet post‐treatment, " summarised evidence about provision of nutritional guidance following diagnosis, but also contrasting views about the role of diet post‐diagnosis. Qualitative studies contributed considerably more to the synthesis, compared to quantitative studies. Included studies were of moderate to good quality; selection bias in quantitative studies and poor evidence of credibility and dependability in qualitative studies were highlighted. Conclusion: There is some evidence of lack of nutrition support in pelvic cancer survivors, but methodological limitations of included studies may have had an impact on the findings. Future, prospective studies that focus on diet and nutrition needs post‐diagnosis are warranted to improve care.